PENGEMBANGAN MEDIA BDA (BOARD DAILY ACTIVITIES) UNTUK MENINGKATKAN HASIL BELAJAR TEMA TUGASKU SEHARI-HARI SISWA KELAS II SD - Arifin Oktavia Sari; Khusnul Fajriyah; Ibnu Fatkhu Royana (Universitas Negeri Medan, 2018)
Abstract : BDA (Board Daily Activities) Media Development to Improve Learning Outcomes Themes of My Second Day Students Secondary School Elementary School. The type of this research is Research and Development (Research and Development). The research population is all students of SDN 01 Ngraji academic year 2017/2018. The sample taken by researchers is 26 students of class II. The data in this research is obtained through observation, interview, test and questionnaire. The results of validation questionnaire analysis conducted by the expert of learning media with percentage of 94.53% with very good category, material learning material with a percentage of 90% with very good category, but got advice given by media validator and material to do attention to do little improvement or revision to make the media more perfect. Test results of practicality and effectiveness performed from 26 students. Obtained average percentage of student interest questionnaire with a percentage of 97.95% of 26 students with very good category. Based on the results of this study suggestions that can be delivered is that BDA learning media can be used as one of the media used by teachers.Keywords : BDA Media (Board Daily Activities)Abstrak : Pengembangan Media BDA (Board Daily Activities) untuk Meningkatkan Hasil Belajar Tema Tugasku Sehari-Hari Siswa Kelas II SD. Jenis penelitian ini adalah Penelitian dan Pengembangan (Research and Development).Populasi penelitian adalah seluruh siswa SDN 01 Ngraji tahun pelajaran 2017/2018. Sampel yang diambil peneliti adalah 26 siswa kelas II. Data dalam penelitian ini diperoleh melalui observasi, wawancara, tes dan angket. Hasil analisis angket validasi yang dilakukan oleh ahli media pembelajaran dengan presentase sebanyak 94,53% dengan kategori sangat baik, ahli materi pembelajaran dengan presentase 90% dengan kategori sangat baik, namun mendapat saran/masukan yang diberikan validator media dan materi untuk melakukan perhatian untuk melakukan sedikit perbaikan atau revisi agar media menjadi lebih sempurna.Hasil pengujian kepraktisan dan keefektivan yang dilakukan dari 26 siswa . Didapatkan rata-rata presentase angket ketertarikan siswa dengan presentase 97,95% dari 26 siswa dengan kategori sangat baik. Berdasarkan hasil penelitian ini saran yang dapat disampaikan adalah supaya media pembelajaran BDA dapat digunakan sebagai salah satu media yang digunakan oleh guru.Kata Kunci : Media BDA (Board Daily Activities)